Admiral Malahayati: The Role of Women in Maritime Defense - Singgih Wiryono; Fauzia Gustarina Cempaka Timur; Almuchalif Suryo (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2025)
Admiral Malahayati, a female figure in the history of the Aceh Sultanate, played a significant role in defending regional sovereignty from colonial threats in the late 16th century. This study explores Malahayati's contribution to naval warfare strategies and community participation, especially war widows, in defense efforts. Using a qualitative approach and theories of maritime war and general warfare, this study analyzes how Malahayati utilized community support and local resources to build an effective military force. The entry of Inong Balee (widows) troops who lost their husbands in the conflict gave a new dimension to the concept of maritime resilience. They not only played a role as logistical support but were also actively involved in the resistance against the invaders. Using the principle of civil society involvement expressed by Reznikova, this study shows that civil society participation, especially the active role of women, is an important element in maintaining a country's sovereignty. The results of this study highlight the importance of integrating the roles of women and society in defense strategies, as well as the significance of Malahayati's history in the context of modern debates about community involvement in national defense, especially among women. These findings are expected to provide new insights into women's contributions to Indonesian military history and open new discussions about national resilience in the face of contemporary threats.